2007
DOI: 10.1055/s-2007-964948
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Prenatally Diagnosed Choledochal Cyst and Type-1 Cystic Biliary Atresia by CD56-Immunostaining Using Liver Biopsy Specimens

Abstract: Because it is difficult to distinguish preoperatively between a prenatally diagnosed choledochal cyst (CC) and type-1 cystic biliary atresia (BA) by ultrasound scanning or magnetic resonance imaging, some mode of discriminating between the 2 entities is required. The aim of this study was to investigate the immunohistological differences between prenatally diagnosed CC and type-1 cystic BA, using liver biopsy specimens immunostained for CD56. Five children with prenatally diagnosed CC and two children with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Other authors have suggested that to assess fibrosis [26] or biliary tract expression of neural cell adhesion molecule 1 (CD56) [27] may permit discrimination, although reported numbers are too small to be conclusive. Radioisotope scans have also been proposed [3,19,24].…”
Section: Discussionmentioning
confidence: 98%
“…Other authors have suggested that to assess fibrosis [26] or biliary tract expression of neural cell adhesion molecule 1 (CD56) [27] may permit discrimination, although reported numbers are too small to be conclusive. Radioisotope scans have also been proposed [3,19,24].…”
Section: Discussionmentioning
confidence: 98%
“…68 Moreover, immunohistochemical analysis of CD56-stained liver biopsy specimens from CC and CBA patients showed no CD56 positivity and less hepatic fibrosis in CC group compared with varying levels of CD56 positive hepatocytes and increased hepatic fibrosis in all prenatally diagnosed CBA. 70,71 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…than the normal development of the bile ducts, could contribute to the stable cyst size in utero [29]. Another theory suggested that overexpression of CD56 at the portal area represented dysregulation of the cell or intercellular matrix interactions in ductal plate remodeling in prenatal cBA patients [30]. These immune and inflammatory responses could affect various features of the size and growth patterns of cysts in cBA and CC prenatally.…”
Section: Discussionmentioning
confidence: 99%